Taking intelligence analysis to the next level : advanced intelligence analysis methodologies using real-world business, crime, military, and terrorism examples - McGlynn, Patrick, 1960- (Boca Raton, FL : CRC Press, 2023)
"Taking Intelligence to the Next Level: Advanced Intelligence Analysis Methodologies Using Real-World Business, Crime, Military, and Terrorism Examples examines intelligence gathering and analysis and the significance of these programs. Coverage assumes a basic understanding of the intelligence cycle and processes, and the book builds upon the author's previous text, Intelligence Analysis Fundamentals-also published by CRC Press-to further address various types of intelligence, the function and increasing usage of intelligence in both the private and public sectors, and the consumption of intelligence products to inform strategic decision-making. Developed for a classroom environment, chapters are packed with multiple examples, visuals, and practical exercises tailored for the intelligence community (IC), military intelligence analyst, criminal, or business analyst alike. The text begins with a chapter on analytical ethics, an important topic that sets the tone for those to come that cover intelligence gathering analytical techniques. The author utilizes multiple instructive learning approaches to build on the student's existing analytical skills gained from other training resources, their experience, or some other combination. While topics covered are germane to all intelligence analysis fields-including military, national, political, criminal, and business-specific chapters and sections and most instructional examples, scenarios, exercises, and learning activities focus on the Homeland Security Mission and the associated problem sets. The training presentation methods and instructional approaches are the product of much thought, research, and discussion, and a variety of US government and commercial analytical training methodologies are presented. The book closes with a final chapter looking at future trends in intelligence analysis. Key Features: Provides tools to challenge intelligence assessments systematically and objectively, a prerequisite to vetted intelligence conclusions Outlines diagnostic techniques to explain events or data sets, anticipate potential outcomes, predict future trends, and make decisions for optimal outcomes Details how to conduct research to effectively write, edit, format, and disseminate reports to best effect An accompany Instructor's Guide, for use in the classroom, contains the same practical exercises as those found in the student text, as well as facilitator's guides, practical exercise solutions, discussion points, sample test questions, and answer keys, to include other websites that can provide additional instructional content. Taking Intelligence to the Next Level serves as an essential course textbook for programs in intelligence, terrorism, and Homeland Security in additional to serving a useful reference for practiving professionals. Ancillaries including PowerPoint lecture slides, as well as the Instructor's Guide with Test Bank, are available for qualified course adopters"--
OCLC-licensed vendor bibliographic record.
Keywords: Business intelligence; Military intelligence; Intelligence service; POLITICAL SCIENCE / Political Freedom & Security / Intelligence; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; POLITICAL SCIENCE / Political Freedom & Security / International Security